Comprehensive assessment as part of the assistive technology service delivery process - Rina Juel Kaptain; Michelle Riisager; Christina Juul; Morten Rye Olsen; Eva Ejlersen Wæhrens (Scandinavian Journal of Occupational Therapy)
Background The assistive technology (AT) service delivery process is complex and includes a comprehensive assessment of the citizen’s situation to inform decision making. This assessment is required by Danish law to ensure that citizens receive solutions matched to their needs, including other services than the AT.Aim To investigate how Danish occupational therapists, involved in the AT service delivery process, perform the comprehensive assessment.Material and methods The study is a cross-sectional survey. The target population was occupational therapists providing AT through the AT service delivery process in municipal units. Data were analysed using descriptive statistics.Results The sample included n = 206 Danish occupational therapists completing the questionnaire. Participants represented the five regions in Denmark. Variations were seen across age, years of working experience, and years in current position. Fifty nine percent of the participants often used telephone interviews, and 74% reported to do home visits to gather information as part of the assessment process. During home visits, participants typically combined methods of interview and observation. Most participants reported not using standardised assessment tools, or not using them in their full length. Almost 80% reported having no guidelines about tool(s) to be used at their workplace. Overall, participants were satisfied with the assessment process.Conclusions When Danish occupational therapists perform comprehensive assessments to ensure that citizens receive solutions matched to their needs, including other services than the AT, the assessment approach and methods employed vary across therapists, since local guidelines for assessment and the use of standardised assessment tools are sparse.Significance To support a high-quality comprehensive assessment process, also ensuring a sustainable client-centred process, a standard minimum guideline is recommended within the Danish AT service delivery system.